Aggressive Management in A Child With Homozygous Familial Hypercholesterolemia - Başpınar, Osman; Kazaz, Hakkı; Dağlar, Bahadır; Bayraktaroğlu, Ziya; Davutoğlu, Vedat; Dai, Alper İ. (European Journal of Therapeutics, 2009)
Homozygous familial hypercholesterolemia is a rare and fatal disease. Twelve year-old girl patient with anginal symptoms and diffuse xanthomas were treated with diet restriction, per oral high dose statins, ezetimibe, low-density lipoprotein cholesterol apheresis and coronary artery bypass grafting. She has been on follow-up visit in stable condition.